ANALISIS PENGARUH WORK FAMILY CONFLICT DAN BEBAN KERJA TERHADAP INTENTION TO QUIT DENGAN STRES KERJA SEBAGAI VARIABEL INTERVENING - Sherli Junianingrum; Fuad Mas’ud Mas’ud (Jurnal Bisnis dan Ekonomi, 2021)
This study aims to analyze the effect of work family conflict, workload on intention to quit with work stress as an intervening variable at Health Insurance. The dependent variable is intention to quit, the independent variable is work family conflict, workload & work stress. The population is all married female employees. Sampling in this study used purposive sampling technique. A valid sample of 145 married female employees was recruited in this study, & participants voluntarily answered online questionnaires. Structural equation modelling analysis were used to examine the relationship between work family conflict, workload, work stress on intention to quit in married female employees. We found that women’s perceptions of both work family conflict & work load were significant positive related to work stress & intention to quit & also work stress were significant positive related to intention to quit. The whole result was significant positive, which supported the hypothesize.